2006
DOI: 10.1016/j.jacc.2006.02.073
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Renal Safety of Isosmolar Iodixanol Compared With Low-Osmolar Contrast Media

Abstract: This meta-analysis of pooled data from 2,727 patients indicates that use of the IOCM iodixanol is associated with smaller rises in Cr and lower rates of CIN than LOCM, especially in patients with CKD or CKD + DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
201
5
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(222 citation statements)
references
References 47 publications
7
201
5
9
Order By: Relevance
“…A pooled analysis of 16 double-blind, randomized, controlled trials (n ¼ 2,727) comparing nephrotoxicity of iso-smolar contrast medium iodixanol with lowosmolar contrast media was recently published [38]. The maximum creatinine increase within 3 days after contrast medium administration was significantly smaller in the iodixanol group compared with the lowosmolar contrast media group (0.06 mg/dL vs. 0.10 mg/dL; P < 0.001).…”
Section: Type Of Contrast Agentmentioning
confidence: 99%
See 1 more Smart Citation
“…A pooled analysis of 16 double-blind, randomized, controlled trials (n ¼ 2,727) comparing nephrotoxicity of iso-smolar contrast medium iodixanol with lowosmolar contrast media was recently published [38]. The maximum creatinine increase within 3 days after contrast medium administration was significantly smaller in the iodixanol group compared with the lowosmolar contrast media group (0.06 mg/dL vs. 0.10 mg/dL; P < 0.001).…”
Section: Type Of Contrast Agentmentioning
confidence: 99%
“…Recent data suggests that use of the isoosmolar iodixanol is associated with smaller rises in creatinine and lower rates of CIN than low-osmolar contrast media, especially in patients with renal insufficiency and with combination of renal insufficiency and diabetes mellitus [38,39].…”
Section: Type Of Contrast Agentmentioning
confidence: 99%
“…10 The incidence of nephrotoxicity is less in iso-osmolar non-ionic contrast medium (e.g Iodixanol) than in lowosmolar non-ionic contrast medium (e.g Iopamidol). 11 But one study by Hossain in Bangladesh has shown that no significant difference between iso-osmolar and low-omolar contrast media in patients with chronic kidney disease(CKD). 12 The lowest rate of CIN occurring in patients receiving less than 100 to 140 ml of contrast media.…”
mentioning
confidence: 99%
“…Intravenous hydration with 0.9% SS) 0.9% SS 1 mL/kg/h, 12 hours before and 12 hours after the procedure Several randomized studies and metaanalyses 30,[32][33][34] 0.9% SS is superior to 0.45% SS 23,32 Sodium bicarbonate (154 mEq/L) NaHCO3 3 mL/kg/h, 1 hour before the procedure and 1 mL/kg/h, 6 hours after the procedure Several randomized studies and meta-analyses 32,[49][50][51][52][53][54] Dilute 154 mL of 8.4% sodium bicarbonate in 846 mL of distilled water for obtaining the solution Type of contrast medium Low-osmolality or iso-osmolality contrast medium Some randomized studies and a few meta-analyses [26][27][28] The literature is still controversial whether isoosmolality contrast medium is superior to low-osmolality contrast medium 29 N-acetyl cysteine 600 mg, orally, 12/12 hours, 24 hours before and after the procedure Still controversial 54,55 Large ongoing multicenter study 56 …”
Section: Most Used Methods Evidence Level Commentsmentioning
confidence: 99%
“…27 McCullough et al have assessed 16 randomized, double-blind studies, in a total of 2,727 patients, and concluded that the use of iso-osmolality contrast medium was better than that of low osmolality contrast medium for preventing CN, mainly in patients with chronic kidney disease and diabetes mellitus. 28 A more recent meta-analysis has compared the use of low-osmolality contrast media with the iso-osmolality contrast medium, iodixanol. It included 16 randomized studies, in a total of 2,763 patients.…”
Section: Osmolalitymentioning
confidence: 99%